Circular RNA 000554 represses epithelial‐mesenchymal transition in breast cancer by regulating microRNA‐182/ZFP36 axis. Issue 9 (30th July 2020) - Mao, Yan; Lv, Meng; Cao, Weihong; Liu, Xiaoyi; Cui, Jian; Wang, Yongmei; Wang, Yuanyuan; Nie, Gang; Liu, Xiangping; Wang, Haibo
Abstract: Increasing evidence indicates that circular RNAs (circRNAs) play a crucial role in regulating microRNAs (miRs) and mRNAs during breast cancer (BC) progression. Based on the in silico analysis of circRNA/miR/mRNA in BC, we aim to define an important role of circRNA_000554 in BC in relation to miR‐182 and zinc finger protein 36 (ZFP36). Low expression of circRNA_000554 and ZFP36, and high miR‐182 expression were determined in the clinical BC tissues. CircRNA_000554 acted as a sponge of miR‐182, and miR‐182 directly targeted ZFP36. After that, in order to evaluate the effects of circRNA_000554, miR‐182, and ZFP36 on cellular process, we evaluated in vitro epithelial‐mesenchymal transition (EMT) and in vivo tumor growth after delivering a series of overexpression plasmids, mimic, inhibitor, or shRNAs into BC cells. Increasing circRNA_000554 suppressed EMT, cell invasion and migration during BC by depleting miR‐182 and increasing ZFP36. The inhibitory effect of circRNA_000554 on tumor growth was validated in vivo. Taken together, the present study confirms that circRNA_000554 functioned as an inhibitor of EMT in BC and suggests a molecular mechanism that circRNA_000554 bound to miR‐182 to upregulate ZFP36 in this process.